Tinjauan Penerapan Konsep Pencahayaan Dengan Pendekatan Lapisan Cahaya Pada Desain Interior Kafe - Isdianto, Fadhil Achmadi (Waca Cipta Ruang, 2024)
Lighting in cafés is a factor that needs to be considered in creating a comfortable and attractive atmosphere for visitors. This study discusses lighting in café interior design using the theory of layered lighting or the "layer approach" concept to understand and explain the interpretation of empirical data collected from a case study of six cafés located in Bintaro Jaya Xchange Mall. The objective of this research is to identify how the layered lighting concept is applied in café interior design and its impact on the comfort of visitors in carrying out activities. This research uses a qualitative approach and descriptive method by analyzing the application of lighting layers based on field observations and analyzing visitors' visual comfort through lighting aspects via interviews. The conclusion of this research is that there is a tendency to use spotlight lighting as the main lighting and indirect strip lighting as ambient, task, and decorative layers. The effect of the focal layer is insignificant because café lighting prioritizes comfort and ambiance. Ambient lighting can also function as both task and decorative layers because, as general lighting, it can determine the atmosphere and aesthetic value of the space. Properly planned and arranged ambient, task, focal, and decorative lighting layers can enhance the emotional and aesthetic atmosphere of the room and enrich the visual experience without putting excessive strain on the eyes.